2017
DOI: 10.1016/j.joco.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of needle stick and sharp injuries and their associations with visual function among hospital nurses

Abstract: PurposeTo determine the one-year incidence of needle stick and sharp injuries (NSIs and SIs) and their associations with visual function among Iranian nurses.MethodsIn this cross-sectional study, 278 nurses working at one hospital were selected through stratified random sampling. After applying the exclusion criteria, the final analysis was performed on the data of 267 nurses. The data of occupational injuries were collected through a researcher-administered questionnaire. Visual function indices including dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
0
13
1
1
Order By: Relevance
“…4,5,7,13,[22][23][24][25][26] This finding is in agreement with the results of many studies that found a high incidence rate of NSSIs among nurses and nursing students. 1,15,16,21,23,24,27 The exact cause of the high proportion of NSSIs among HCWs, including nurses, is unknown but could be related to several factors. It is possible that the public in Jordan and many other developing countries prefer injections over other methods for the delivery of drugs and pharmaceuticals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,7,13,[22][23][24][25][26] This finding is in agreement with the results of many studies that found a high incidence rate of NSSIs among nurses and nursing students. 1,15,16,21,23,24,27 The exact cause of the high proportion of NSSIs among HCWs, including nurses, is unknown but could be related to several factors. It is possible that the public in Jordan and many other developing countries prefer injections over other methods for the delivery of drugs and pharmaceuticals.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Few studies have examined NSSIs in Jordan and most have only included data collected from practicing nurses or nursing students. 10,[13][14][15] These studies concluded that NSSI rates are high among nurses and nursing students, the level of awareness of universal precaution guidelines is low, reporting occupational exposures to NSSIs is inadequate and young female nurses with fewer years of experience are more vulnerable to NSSIs. 10,[13][14][15] Studies on the proportion of NSSIs among HCWs, except nurses, have not been conducted in Jordan.…”
mentioning
confidence: 99%
“…A self-administered questionnaire was designed by the researchers after reviewing the related literature. 1,2,4,7 The questionnaire was written in English and comprised questions about nurses' demographic data and SIs circumstances. SIs stress was measured using the Impact of Event Scale-Revised (IES-R) and the PTSSQI.…”
Section: Data Collection Processmentioning
confidence: 99%
“…[1][2][3][4][5][6] Working in acute care units is considered an important factor for the occurrence of SIs as noted by many studies. 1,2 SIs can lead to acquiring life-threatening viral infections, the economic burden of medical care for the affected individuals, and possible loss of jobs. [3][4][5] Stress is a major occupational hazard in the nursing profession, and it has been implicated for absence from jobs, productivity reduction, displacement of personnel, work conflicts, and higher health care costs for employees.…”
Section: Introductionmentioning
confidence: 99%
“…Untuk sistem surveilans dengan tradisional mempunyai kelemahan dalam penerapan dan pelaksanaannya salah satunya adalah proses pengumpulan data manual yang memakan waktu dan sumber daya yang banyak (Mahomed, Mahomed, Sturm, Knight, & Moodley, 2017 Pelaksanaan sistem pencatatan surveilens dengan menggunakan paper based ditemukan bahwa perawat merasakan formulir pengawasan ini menambah beban kerja mereka, dalam mengumpulkan data tidak konsisten, sementara data harus terisis setiap harinya, begitu juga dengan tim penegndali infeksi tidak mampu secara memadai mengawasi proses tersebut ke seluruh ruangan di rumah sakit karena tuntutan pekerjaan yang lainnya. Ghasemi, Khabazkhoob, Hashemi, Yekta, & Nabovati (2017) Berdasarkan hasil analisis dari hasil uji beda sistem pencatatan dengan elektronik dan paper based, didapatkan hasil pencatatan dengan menggunakan paper based mempunyai perbedaan signifikan dengan sistem berbasis elektronik (pvalue=0.000). Meskipun data yang disimpan dalam sebuah system surveilans berbasis elektronik belum spesifik, namun cukup sensitif dalam hal penyimpanan data dan mudah untuk dikaitkan dengan kebutuhan lain dalam surveilans (Bruin, Seeling, Schuh, 2014 Peneliti menyimpulkan bahwa kendala utama dari penggunaan sistem otomatis/elektronik dalam surveilens infeksi adalah keragu-raguan dalam melaksanakan tugas, tanggung jawab, metode cara kerja, harapan pengguna, menjadi penghambat kenapa adopsi sistem ini lambat.…”
Section: Pendahuluanunclassified